Anti-metastatic effect of ranolazine in an in vivo rat model of prostate cancer, and expression of voltage-gated sodium channel protein in human prostate - Bugan, İlknur; Küçük, Selma; Karagöz, Zeynep; Fraser, SP; Kaya, Handan; Dodson; Foster, Cs; Djamgoz, Mba; ALTUN, SEYHAN (My University, 2019)
Background Voltage-gated Na+ channels (VGSCs) are functionally upregulated in rat and human prostate cancer (PCa) where channel activity promotes cellular invasiveness in vitro and metastasis in vivo. Ranolazine is a clinically used VGSC inhibitor/anti-anginal drug, which has been shown previously to inhibit breast cancer metastasis in vivo. Methods Using the Dunning model of rat PCa, the effect of ranolazine applied systemically (by gavage) was tested on the development of primary tumours and metastases following subcutaneous inoculation of Mat-LyLu cells into Copenhagen rats. In addition, human prostate tissue microarrays were used to determine VGSC protein expression in cancerous versus non-cancerous tissue. Several public databases were searched to compare Nav1.7/ SCN9A expression levels in ‘normal’ vs. PCa tissues. Results Ranolazine (2.5 and 5 µM) decreased the number of lung metastases by up to 63%. In contrast, primary tumourigenesis was not affected. Ranolazine also reduced the percentage of cells in the metastases expressing Nav1.7, the main VGSC subtype expressed in PCa, but the expression level was higher. In prostate tissue microarrays, VGSC protein expression was significantly higher in cancerous versus non-cancerous tissue. There was no correlation between the VGSC expression and either prostate-specific antigen or Gleason score. In public databases, little information could be found on Nav1.7 protein expression in PCa. In addition, the database information on Nav1.7 mRNA (SCN9A) expression levels did not correlate with previously reported upregulation in PCa cells and tissues. Conclusions The main conclusions were (i) ranolazine inhibited metastasis and (ii) it was a subpopulation of cells with particularly high levels of Nav1.7 protein that reached the metastatic sites. These data extend earlier studies and suggest that Nav1.7 expression could serve as a functional biomarker of metastatic PCa and that VGSC blockers may be useful as antimetastatic agents.